Transforming Traditional Farmers into Professionals: An Introduction to Human Resource Management in Rural - Yohny Anwar; Venti Jatsiyah; M. Zahari; Arif Saefudin; Nofirman Nofirman (Postgraduate, University of Mataram, 2023)
This research is focused on outlining experiences in rural human resource management through the introduction of a new professional farmer training process. The aim is to provide insights and references for developing countries in implementing farmer training and improving their human resource structure. The research methodology explores the literature combined with an inductive approach to describe and analyse experiences and lessons learned during training programmes to strengthen human resource capacity in the agricultural sector. The results of this study emphasise the importance of new professional farmer training in rural human resource management, with the Indonesian government prioritising the entire training process. The Indonesian government has taken strategic steps in farmer training, which include identifying appropriate training targets, selecting influential investment entities, developing practical training models, and designing supportive policies. These initiatives have significantly improved the quality and structure of rural human resources. The uniqueness of this research lies in its selection of topics that are less widely covered in the literature, especially regarding the training process and the new professional farmer model. This research is also important in enhancing the skills of rural individuals, increasing farmers' income, strengthening the role of agriculture, and supporting economic growth in rural areas. Furthermore, this research makes a significant contribution to the literature by enriching the theory of human capital investment in rural areas.